S Semiotika Perundungan Digital: Membedah Konstruksi Identitas Siswa dalam “Toxic Language” Game Online sebagai Dasar Inovasi Layanan Bimbingan dan Konseling - Novia Damayanti (Universitas Veteran Bangun Nusantara, 2026)
The phenomenon of cyberbullying through the use of toxic language in online games has penetrated into students' daily verbal interactions at school, potentially eroding the psychological climate of the educational environment. This study aims to dissect the semiotic meaning of cyberbullying in online game toxic language while mapping how this language constructs students' social identity at school. The method used is descriptive qualitative involving a total of 36 students. Informant selection applied purposive sampling technique, while data collection was conducted through documentation of in-game chat screenshots and in-depth interviews. The data analysis technique utilized Roland Barthes' semiotics two-order of signification model to unravel denotation, connotation, and myth. The results show variations of verbal aggression divided into clusters of skill insults, harsh/expletive swear words, sarcasm, and personal domestic attacks. Semiotic analysis proves the occurrence of connotative operations that transform technical game terms into symbols of inferiority, semantic normalization of cursing as a group catharsis, and deconstruction of self-esteem through the exploitation of social status. Mythologically, this shapes a youth subculture ideology that normalizes verbal aggression (online disinhibition effect). Although the psychological impact remains within safe limits, students proactively demand school counselors to understand their gaming world terms as a basis for innovative and adaptive guidance and counseling services.